Ploidy and genome composition of Musa germplasm at the International Institute of Tropical Agriculture (IITA) - Pillay, M.; Ogundiwin, E.; Tenkouano, A.; Doležel, Jaroslav (2006)
Musa spp (bananas and plantains) constitute a hybrid-polyploid complex and are classified according to different genome compositions such as AA, BB, AB, AAA, AAB, ABB, AAAA, ABBB, AAAB and AABB. Knowledge of ploidy and exact genome compositions of the parental material is essential for Musa breeding. This study determined the ploidy levels and genome composition of the Musa germplasm collection, constituting over 300 accessions, at the International Institute of Tropical Agriculture in Nigeria and Uganda. Flow cytometric analysis of nuclear DNA content was used to estimate ploidy levels, while genome composition was ascertained with RAPD markers that are specific for the A and B genomes of Musa. It was determined that at least 8% of the plants in the germplasm collection were miss-classified in terms of ploidy and/or genome composition. The cultivars 'Pisang awak', 'Foulah 4' and 'Nzizi', previously classified as triploids, were found to be tetraploids by flow cytometry and conventional root tip chromosome counts. Similarly, cultivars that were previously classified as diploids including 'Too', and 'Toowoolee' were found to be triploids in our analysis. Ploidy and genome classification in Musa was generally determined from morphological characteristics. While our study showed that such a system is not always reliable, it was interesting to find that none of the plantains in the germplasm collection were miss-classified with regards to both ploidy and genome composition.